2019
DOI: 10.1038/s41598-019-44217-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of silencing expression of myostatin (MSTN) and its two receptors (ACVR2A and ACVR2B) genes affecting growth traits in knock down chicken

Abstract: Myostatin (MSTN), a growth differentiation factor-8 regulates muscular development through its receptors, ACVR2A (Activin receptor type IIA) and ACVR2B (Activin receptor type IIB) by inhibiting cellular differentiation of developing somites during embryonic stage and diminishing myofibriller growth during post-embryonic period. The objective of this study was to compare the effect of knockdown of expression of myostatin, ACVR2A and ACVR2B genes on growth traits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
1
26
0
4
Order By: Relevance
“…In C42del/C42del quail, increased muscle mass was caused by muscle fiber hyperplasia, rather than fiber hypertrophy. In addition, muscle fiber hyperplasia was also observed in MSTN knockdown chickens [22]. Although both C42del/C42del quail and MSTN knockdown chickens are not complete MSTN knockout avian models, the data suggests that disruption of the MSTN gene in the avian species will increase muscle mass with muscle fiber hyperplasia, rather than fiber hypertrophy or both.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In C42del/C42del quail, increased muscle mass was caused by muscle fiber hyperplasia, rather than fiber hypertrophy. In addition, muscle fiber hyperplasia was also observed in MSTN knockdown chickens [22]. Although both C42del/C42del quail and MSTN knockdown chickens are not complete MSTN knockout avian models, the data suggests that disruption of the MSTN gene in the avian species will increase muscle mass with muscle fiber hyperplasia, rather than fiber hypertrophy or both.…”
Section: Discussionmentioning
confidence: 93%
“…The function of MSTN seems to be conserved in avian species as a recent study showed increased muscle mass in MSTN knockdown chickens [22]. To consolidate the anti-myogenic function of MSTN in avian species, an in vivo effect of MSTN mutation on avian muscle growth should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The Mstn/ Activin branch of the TGF- family is very ancient and is present in some pre-Bilateria groups including several cnidarian species (Watanabe, et al, 2014), but functional studies of its role in muscle size control in these animals are lacking. In fact, Mstn's role in muscle growth has only been studied in a few other non-mammalian vertebrates including chickens, turkeys and zebrafish where the results mirror the mammalian case (Bhattacharya, et al, 2019;Gao, et al, 2016;McFarland, et al, 2006). As for invertebrates, there are two published reports, one using the giant prawn Macrobrachium rosenbergii (Easwvaran, et al, 2019) and the other the penaeid shrimp Penaeus monodon (De Santis, et al, 2011).…”
Section: Activin Signaling On Mammalian Verses Drosophila Somatic Musmentioning
confidence: 99%
“…Among these, Myostatin (Mstn), a member of the TGF- superfamily of growth and differentiation factors, has proven to be a prominent player. Loss-of-function mutations in mstn have been identified or induced in a large variety of mammals including mice, cattle, dogs, sheep and humans (Clop et al, 2006;Kambadur et al, 1997;Mosher et al, 2007;Schuelke et al, 2004) as well as birds and fish (Bhattacharya et al, 2019;Gao et al, 2016;McFarland et al, 2006). In all these species, loss of mstn results in larger skeletal muscles leading to the conclusion that Mstn is a negative regulator of muscle mass.…”
Section: Introductionmentioning
confidence: 99%
“…The protein isolated from magnum tissues was run on SDS-PAGE following standard method (Bhattacharya et al, 2019). The proteins separated in SDS-PAGE were transferred into 0.45µm polyvinylidene fluoride (PVDF) membrane.…”
Section: Western Blottingmentioning
confidence: 99%